2012
DOI: 10.1186/1744-9081-8-61
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic neuroactive steroids: a new frontier in bipolar disorders?

Abstract: Neurosteroids are synthesized in the brain and modulate brain excitability. There is increasing evidence of their sedative, anesthetic and antiseizure properties, as well as their influence on mood. Currently neurosteroids are classified as pregnane neurosteroids (allopregnanolone and allotetrahydrodeoxycorticosterone), androstane neurosteroids (androstanediol and etiocholanone) or sulfated neurosteroids (pregnenolone sulfate and dehydroepiandrosterone sulfate). Both preclinical and clinical findings indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 93 publications
1
42
0
1
Order By: Relevance
“…Not much is known about how cortisol might influence the level of neuroactive steroid hormones deriving from progesterone, or rather their analogues sulfates, or testosterone, which apparently have a different effect on mood [21]. Indeed, a recent study found that in the elderly, the perception of Quality of Life was not affected by testosterone levels [22].…”
Section: Discussionmentioning
confidence: 99%
“…Not much is known about how cortisol might influence the level of neuroactive steroid hormones deriving from progesterone, or rather their analogues sulfates, or testosterone, which apparently have a different effect on mood [21]. Indeed, a recent study found that in the elderly, the perception of Quality of Life was not affected by testosterone levels [22].…”
Section: Discussionmentioning
confidence: 99%
“…Both preclinical and human data suggest that pregnenolone may be a promising treatment for bipolar depression (Carta et al, 2012;Marx et al, 2009;Ritsner et al, 2010). Pregnenolone is an endogenous neurosteroid (Baulieu, 1998) that is a precursor to numerous other downstream steroids, including cortisol, allopregnanolone, dehydroepiandrosterone (DHEA), and progesterone.…”
Section: Introductionmentioning
confidence: 99%
“…Установлено, что стероидогенез может протекать и за пределами желез внутренней секреции, в частности, в головном мозге, коже и адипоцитах. Стероиды, способные оказывать быстрые негеномные эффекты на мозг и пове-дение, называют нейроактивными, а те из них, которые синтезируются в мозге de novo, -ней-ростероидами Dubrovsky, 2005;Follesa et al, 2006;Mensah-Nyagan et al, 2008;Carta et al, 2012;Schiller et al, 2014].…”
Section: общие сведения о стероидных гормонахunclassified